The role of phonological awareness and phonetic radical awareness in acquiring Chinese literacy skills in learners of Chinese as a second language - Zhang, Haiwei; Leah Roberts (System, 2019)
There is much research into the roles of phonological awareness and phonetic radical awareness in the development of Chinese character reading and writing skills in native-speaking children, but there is comparatively little work on the relationship between such metalinguistic skills and character literacy skills in adult learners of Chinese a second language (CSL). In this study, we explored this issue with 83 Arabic and English CSL learners who had studied Chinese in their home country. Their knowledge of phonological awareness, phonetic radical awareness, and Chinese character reading and writing was measured. There were two main findings. Firstly, the learners’ phonological awareness, but not their phonetic radical awareness, predicted the acquisition of character reading and writing skills directly or indirectly. Secondly, phonetic radical awareness did not mediate the effect of phonological awareness on character reading and writing skills. The results point to the different roles that phonological awareness and phonetic radical awareness play in the development of character literacy skills, and the still unclear relationship between phonological awareness and phonetic radical awareness. These findings are important for understanding the contribution of phonological awareness and phonetic radical awareness to the acquisition of character literacy skills for CSL learners.
Keywords: Chinese character; Metalinguistic awareness; Phonetic radical awareness; Phonological Awareness; Second language acquisition